Production of bioethanol from apple pomace by using cocultures: Conversion of agro-industrial waste to value added product. (August 2015) - Evcan, Ezgi; Tari, Canan
Abstract: Direct fermentation of cellulosic biomass to bioethanol has been very promising and hence attracted attention in recent years. In this study, bioethanol production from apple pomace hydrolysate (agro-industrial waste product) was investigated by coculturing Trichoderma harzianum, Aspergillus sojae and Saccharomyces cerevisiae using statistical approaches. Screening and optimization experiments were conducted in order to determine the significant factors and their optimum levels for maximum bioethanol production. Inoculation rates, aeration and agitation speed were considered as factor variables and bioethanol production as response variable. Highest bioethanol (EtOH) concentration and ethanol yield on total reducing sugar content (YP/S ) were 8.748 g/L and 0.945 g/g, respectively. Optimum conditions were 6% (w/v) inoculation rates of T.harzianum and A.sojae, and 4% (v/v) inoculation rate of S.cerevisiae with vented aeration method and agitation speed of 200 rpm. To best of our knowledge to date, no reports are available in literature regarding the coculturing of T.harzianum, A.sojae and S.cerevisiae for bioethanol production. Therefore, this study will serve as a base line of initial studies in this field. The method can create a renewable alternative feedstock for fossil fuel production and suggest a feasible solution to multiple environmental problems simultaneously creating a sink for waste utilization. Highlights: Production of bioethanol from low-cost agro industrial waste product (apple pomace). Coculturing Trichoderma harzianum, Aspergillus sojae and Saccharomyces cerevisiae. Effective way of bioethanol production through the application of coculturing Elimination of waste by turning it into value added product. Alternative way of producing biofuel.